A vontade legisladora enquanto poder limitador das inclinações na filosofia moral de Immanuel Kant - Figueiredo, Rodrigo Lopes (2020)
Achieve a level of compliance with the moral law that makes possible the transition from the inclined will to autonomous will, called legislator on moral issues, this is a challenge we now take on this research. In this sense we reflect on how it is possible for human will rise as a legislative will if in our choices we are constantly driven to counter the moral law present in us, living according to contrary motives and mobiles a priori principles of determining morality. When confronted with the natural influence of inclinations in the human will, Immanuel Kant investigates reason in its speculative and practical dimensions, seeking a stable and unconditional parameter of the foundation of morality. In the opus Groundwork of the Metaphysics of Morals the philosopher develops the notion of Categorical Imperative, denominating it the supreme principle of the morality. In the identification process of this principle, Kant disqualifies any sensible object, empirical concept and subjective condition relative to experience, showing that, within the realm of empirical contingency, it is impossible to arrive at the intended principle. Considering the path traveled by the thinker, our study tries to understand why the natural mobiles are considered factors incompatible with the foundation of morality, even when exercising considerable influence about will. Such a subject is of great importance in our day. Our trajectory begins with the opus Groundwork of the Metaphysics of the Morals (1785), Practical Anthropology (1785) and Religion whithin the limits of reason alone (1793) Throughtout the reconstruction of kantian arguments we to verify how the "mechanism of limitation" of natural mobiles occurs through a priori rational determination; in the course of our studies we will investigate the importance of respect (the moral law) associated with the agent's autonomy when s/he recognizes dignity in her/himself and in others. Finally we arrive at the notion of virtue as a "axiological factor" directed at the person, considered in ones´s human dignity as an end in itself, independent of any practical-instrumental choice, we see there the practical determination ordered by the autonomous will and that coincides with the reasoning sought in the Categorical Imperative.In concret terms: virtue translates the presence of moral value present in the character capable of overcoming impulses and inclinations in a pragmatic self-clarification process.